2021
DOI: 10.3390/cancers13071493
|View full text |Cite
|
Sign up to set email alerts
|

Circulating let-7e-5p, miR-106a-5p, miR-28-3p, and miR-542-5p as a Promising microRNA Signature for the Detection of Colorectal Cancer

Abstract: Colorectal cancer (CRC) is a disease with high incidence and mortality. Colonoscopy is a gold standard among tests used for CRC traceability. However, serious complications, such as colon perforation, may occur. Non-invasive diagnostic procedures are an unmet need. We aimed to identify a plasma microRNA (miRNA) signature for CRC detection. Plasma samples were obtained from subjects (n = 109) at different stages of colorectal carcinogenesis. The patients were stratified into a non-cancer (27 healthy volunteers,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 57 publications
0
24
0
1
Order By: Relevance
“…We found that high glucose increased miR-106a-5p in HUVECs. MiR-106a-5p, a member of miRNA family, plays the molecular regulatory role in multiple sclerosis, colorectal cancer and other chronic diseases [ 27 – 29 ]. Commonly, mmu_circ_0001052 could be involved in cell process by targeting miRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…We found that high glucose increased miR-106a-5p in HUVECs. MiR-106a-5p, a member of miRNA family, plays the molecular regulatory role in multiple sclerosis, colorectal cancer and other chronic diseases [ 27 – 29 ]. Commonly, mmu_circ_0001052 could be involved in cell process by targeting miRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…Several exosomal miRNAs have also been found differentially expressed in CRC patients and reported as potential biomarkers for the CRC clinical diagnosis [ 53 55 ]. A study by Karimi et al identified 11 miRNAs and found that out of these 11 miRNAs, the expression of miR-23a and miR-301a was significantly higher in serum exosomes from CRC patients as compared to healthy controls [ 56 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that let-7e-5p was significantly downregulated and let-7e-5p inhibited tumorigenesis and aggressive behavior in head and neck squamous cell carcinoma and non-small cell lung cancer [ 25 , 26 ]. Conversely, let-7e-5p was significantly upregulated in young patients with oral cavity cancer, colorectal cancer, and rectal carcinoma with liver metastases and promoted the tumorigenesis and aggressive behavior of cancer cells [ 27 29 ]. Similarly, let-7e-5p was overexpressed in thyroid cancer cells, and a high level of let-7e-5p was correlated with poor prognosis.…”
Section: Discussionmentioning
confidence: 99%